ARE AWARENESS CAMPAIGNS EFFECTIVE IN INCREASING UPTAKE OF CERVICAL CANCER SCREENING TEST BY WOMEN: A STUDY IN A MUNICIPALITY IN CENTRAL NEPAL? - Sharma, Kalpana; Kumar Ranabhat, Sabin; Anwar Khan, Gulam; Chaudhary, Sanjeev; Murti Bhurtyal, Karma (Journal of Chitwan Medical College, 2024)
Background: Cervical cancer is one of the most common cancers and a leading cause of mortality among Nepalese women, but almost completely preventable by a screening test. This study aimed to find out the association of knowledge and attitude about cervical cancer and its screening test on the uptake of cervical pap smear test. Methods: A cross-sectional study was carried out among women aged 20 to 65 years residing in Madi Municipality located in the central region of Nepal. Probability systematic sampling technique was used to select 300 samples for the study. Data were collected using structured interview schedule, and these were analysed in IBM SPSS version 20 for windows using descriptive and inferential statistics. Results: Out of 300 married women, median age (IQR) was 40 (54-32) years. Despite 42.7% women having adequate knowledge about cervical cancer and 49% women having favourable attitude towards cervical pap smear, only 6.7% participants had undergone cervical pap smear test at least once in their life. There was no significant association between knowledge about cervical cancer and pap smear, and pap smear utilization. This shows that good knowledge does not always translate into action. Conclusions: Population-based organized cervical pap smear screening program must be implemented to increase pap smear utilization. Health awareness campaigns in the absence of organized cervical screening program are largely ineffective.